(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The paper dwells on the analysis of the problem of image of charismatic personality in modern youth in the context of the project paradigm. The author examines the psychological content and main components of this concept, from the point of view of various scientific schools. The paper elucidates the results of empirical research of the representation of young men about the image of a charismatic personality, namely: understanding the content of this concept, its main characteristics and components, values, motivations of behavior. In addition, the researchers expressed their opinion on the possibility of developing charisma as an important component of self-design in each personality